Superiorly based subperiosteal orbital abscess: an uncommon presentation. Issue 2 (18th February 2021) - Chrysovitsiotis, Georgios; Kollia, Paraskevi; Kyrodimos, Efthymios; Chrysovergis, Aristeidis
Abstract : A 32-year-old female patient presented with severe facial pain, right eye proptosis and diplopia. Endoscopy revealed ipsilateral crusting, purulent discharge and bilateral nasal polyps. Imaging demonstrated a subperiosteal abscess on the roof of the right orbit. Due to patient's significant ocular manifestations, surgical management was decided. The abscess was drained using combined endoscopic and external approach, via a Lynch-Howarth incision. Following rapid postoperative improvement, patient's regular follow-up remains uneventful. A subperiosteal orbital abscess is a severe complication of rhinosinusitis that can ultimately endanger a patient's vision. It is most commonly located on the medial orbital wall, resulting from direct spread of infection from the ethmoid cells. The rather uncommon superiorly based subperiosteal abscess occurs superiorly to the frontoethmoidal suture line, with frontal sinusitis being its main cause. Treating it solely endoscopically is more challenging than in medial wall abscesses, and a combined approach is often necessary.